RELEVANSI KEBAHAGIAAN OTENTIK DALAM MENCEGAH DAN MENANGKAL RADIKALISME PADA MASYARAKAT KAMPUS: TINJAUAN PSIKOLOGI POSITIF - Manurung, Antonius Dieben Robinson; Kanumoyoso, Bondan (Jurnal Pembumian Pancasila, 2024)
This study aims to identify, describe, and analyze a positive psychological approach through authentic happiness in an effort to prevent and ward off radicalism in campus communities (universities) in the DKI Jakarta area. This research used a qualitative approach with a phenomenological study through the focus group discussion technique. The validity of the research will be obtained through credibility, transferability, dependability, and confirmatory research data. totaling 10 people (source persons). The research question that wants to be answered in this research is the importance of a positive psychological approach through authentic happiness to provide positive support in an effort to prevent and ward off radicalism among the campus community in the DKI Jakarta. The results of this research: 1) obtained a comprehensive and in-depth picture of the latent dangers and manifestations of radicalism that can develop in the campus community, 2) a positive psychological approach can be used through a development plan for the application of authentic happiness models in an effort to prevent and warding off radicalism among the campus community in the Jakarta, and 3) developing a more adaptive Pancasila grounding strategy in solving the problem of radicalism in campus communities in the Jakarta.